2012
DOI: 10.1002/gps.3834
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of entorhinal cortex atrophy between early‐onset and late‐onset Alzheimer's disease using the VSRAD, a specific and sensitive voxel‐based morphometry

Abstract: The present study using the VSRAD suggests that early-onset AD shows less atrophy in the entorhinal cortex than late-onset AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The atrophy rates in the volumes of the bilateral EC and amygdala were also associated with the time of symptom onset (Soldan et al, 2015). Patients with mild to moderate AD had a thinner EC than those with MCI (Shibuya et al, 2013;Velayudhan et al, 2013). Thus, the thickness of EC can indicate the severity of the disease and predict the slope of the degree of decline observed in tests of memory performance.…”
Section: Relationship Between Ec Atrophy and The Severity Of Admentioning
confidence: 93%
See 3 more Smart Citations
“…The atrophy rates in the volumes of the bilateral EC and amygdala were also associated with the time of symptom onset (Soldan et al, 2015). Patients with mild to moderate AD had a thinner EC than those with MCI (Shibuya et al, 2013;Velayudhan et al, 2013). Thus, the thickness of EC can indicate the severity of the disease and predict the slope of the degree of decline observed in tests of memory performance.…”
Section: Relationship Between Ec Atrophy and The Severity Of Admentioning
confidence: 93%
“…Du et al (2004) also found that the atrophy rates in the EC and hippocampus in patients with mild AD were positively correlated with memory deficits at baseline that were measured by delayed list recall; this evidence is in line with the conclusion of Stoub et al (Du et al, 2004;Stoub et al, 2010). Shibuya et al found that patients with early-onset AD exhibited less atrophy in EC than those with late-onset AD, but there was no significant difference in memory impairment, which was Brought to you by | Bibliotheque de l'Universite Laval Authenticated Download Date | 10/9/15 6:28 AM measured by the Alzheimer's Disease Assessment Scale (ADAS) word recall subtests, between the two subtypes (Shibuya et al, 2013). There are several potential reasons for the two different conclusions discussed previously:…”
Section: Relationship Between Ec Atrophy and The Severity Of Admentioning
confidence: 94%
See 2 more Smart Citations
“…Prediction of conversion from MCI to AD using initial neuroimaging studies is an important research topic (Matsuda, 2007b;Shibuya et al, 2013). SPECT imaging using N-isopropyl-p-[I-123] iodoamphetamine (I-123 IMP) and graph plot analysis is a simple and convenient way to measure and compare regional cerebral blood flow (rCBF) among patient groups and within the same group during follow-up.…”
Section: Neuroimaging Proceduresmentioning
confidence: 99%